Sex Education: The Present and the Possible Identities. From Postmodernism toward Posthumanism - Giniotaitė, Akvilė (Acta Paedagogica Vilnensia, 2018)
[article in Lithuanian; only abstract and key words in English] The spectrum of identity possibilities based on the gender factor is way larger than the normative sočiety recognizes. In most of the cases, we adopt our sexuality from an already existing model. Gender, as part of our identity, is not being considered and is normative. Posthumanism discusses the difference and the singularity of every subject, and that a human being is more than ever connected with the global processes; an individual can no longer be disconnected from the whole global movement. Gender, from an identity point of view, is scarcely discussed in Lithuania, and posthumanism, which analyzes the newest motions of the global processes, is, too, almost never applied.